PRELIMINARY ASSESSMENT OF YEAST (Saccharomyces cerevisiae) PRODUCTS ON AFRICAN CATFISH PRODUCTION AND HEALTH - BADRU, K.O; ADEOYE, A.A; OBASA, S.O; OLANIYI , M.O; AGBEBI, O.T. (Nigerian Journal of Fisheries, 2019)
A preliminary study was conducted to evaluate the effects of four products of yeast (Saccharomyces cerevisiae) on African catfish production and health. The catfish (11.770.05 g fish-1 , 100 fish 857L tank-1) were fed either of diets supplemented with 0% yeast product (Con), 3% unextracted yeast (UnY), 0.3% hydrolysed yeast (HyY),0.2% mannan-oligosaccharides (MoS) or 0.02% beta-glucan (Bg-S). After 63 days of feeding to apparent satiation, there was no significant difference (P < 0.05) observed in the final body weights, feed conversion ratios, specific growth rates, protein efficiency ratios and survivals of the catfish fed diets supplemented with the yeast products and those fed the control diet. Similarly, the somatic indices and haematological parameters measured were not significantly different (P > 0.05) among the catfish fed the experimental diets. It could be inferred from this study that yeast products (at current levels of inclusion) do not negatively affect the production nor impair the health of African catfish. However, a follow-up dose-response trial will be very informative for comprehensive assessment of each of the yeast products on African catfish production and health.